Implementasi Pembelajaran Akidah Akhlah dalam Pembinaan Adab Belajar Peserta Didik Kelas X Di MA Pancasila Kota Bengkulu - Piki Alamsyah; Wiwinda Wiwinda; Adi Saputra (GHAITSA : Islamic Education Journal, 2024)
The background of this research is to find out how to develop student learning etiquette, the importance of etiquette for a student so that gaining knowledge can facilitate the learning process and make that knowledge useful. The aim of this research is to describe the implementation of learning moral beliefs in developing learning etiquette for class This research uses field research with a qualitative approach. The method used is descriptive research. The subjects in this research were Aqidah Akhlak subject teachers and student representatives at MA Pancasila, Bengkulu City. The object of this research is the Implementation of Moral Creed Learning in the Development of Learning Manners for Class X Students at MA Pancasila, Bengkulu City. Data collection techniques use observation, interviews and documentation. Based on the research results, it can be concluded that the Implementation of Moral Creed Learning in the Development of Learning Manners for Class polite and civilized to teachers and friends, serious about studying, present on time, students obey the rules at school. Meanwhile, the supporting and inhibiting factors are the school, community and family environmental factors in the dormitory.